2020
DOI: 10.1111/apm.13037
|View full text |Cite
|
Sign up to set email alerts
|

Minimal residual disease monitoring cannot fully replace bone marrow morphology in assessing disease status in pediatric acute lymphoblastic leukemia

Abstract: Minimal residual disease monitoring cannot fully replace bone marrow morphology in assessing disease status in pediatric acute lymphoblastic leukemia. APMIS 2020; 128: 414-419.Minimal residual disease (MRD) monitoring has a strong prognostic value in childhood lymphoblastic leukemia (ALL) and is currently utilized in all major pediatric ALL protocols. MRD monitoring is done by multiparameter flow cytometry, IG/TCR quantitative PCR or reverse transcriptase quantitative PCR of leukemic fusion transcripts providi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Despite the current use of flow cytometry and quantitative PCR test for MRD assessment, recently, there were very few studies highlighting the need for post-induction bone marrow examination to monitor residual disease status in addition to the present study. Rathe et al reported the importance of a complete bone marrow examination (aspirate, imprint, and trephine biopsy) along with IHC in post-induction remission assessment of ALL cases, in addition to the flow cytometry and quantitative PCR, which failed to detect MRD [ 14 ]. Similarly, another study (sample size=246) highlighted the role of bone marrow examination (especially bone marrow biopsy) for the morphologic assessment of residual disease in AML [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the current use of flow cytometry and quantitative PCR test for MRD assessment, recently, there were very few studies highlighting the need for post-induction bone marrow examination to monitor residual disease status in addition to the present study. Rathe et al reported the importance of a complete bone marrow examination (aspirate, imprint, and trephine biopsy) along with IHC in post-induction remission assessment of ALL cases, in addition to the flow cytometry and quantitative PCR, which failed to detect MRD [ 14 ]. Similarly, another study (sample size=246) highlighted the role of bone marrow examination (especially bone marrow biopsy) for the morphologic assessment of residual disease in AML [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also true that MRD value may very low, e.g., less than 1% by MFC and molecular methods, while there is resistant disease with more than 20% B-lymphoblasts, as reported by Rathe, et al [16]. Despite MRD monitoring by MFC and NGS cannot fully replace bone marrow morphology in assessing disease status in acute leukemias, as recommended in a series of case report by Rathe [16], the finding in our study and others indicate the limitation of morphologic evaluation on B-ALL residual disease evaluation. Clusters of immature B-cells may not necessary indicate residual leukemic cells and could represent regenerate B-cell precursors.…”
Section: Ngs Evaluation For B-all Mrdmentioning
confidence: 74%